2016
DOI: 10.2320/matertrans.m2016070
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Partial Remelting on Microstructure of Al-Si-Ti Bulk Alloy Prepared by Cold Pressing Mixed Powders

Abstract: The microstructural evolution and phase transformations have been investigated during the partial remelting of a bulk alloy prepared by the cold pressing of A356, pure Ti and pure Al powders. A dropping experiment was used to investigate the reaction kinetics of Ti powders and the Al matrix simultaneously. The results show that a semi-solid microstructure with ne and spheroidal primary α-Al particles suspended in the liquid phase could be obtained after the bulk alloy was heated to 595 C for 30 min. The micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 30 publications
2
10
0
Order By: Relevance
“…In addition, it was found that the distribution of the jagged structures for some reinforcements in the composites was different from that in the semisolid ingots prior to thixoforming, the jagged structures in the composites partially broke away from the core-shell structured particles and individually embedded in the matrix as shown by Figure 9, while they all compactly surrounded the core-shell particles similar to those shown by Figure 7. This implied that the bonding between the jagged structures and the shells was relatively weak, which was consistent to the result that there is always a gap between them and the gap is filled by Al matrix for the reinforcements in the semisolid ingots [14]. During thixoforming, the jagged structures peeled off from the inner core-shell structured particles and then moved away incorporating the liquid phase adjacent to them, resulting in the microstructure shown by Figure 9.…”
Section: Figures Of Metals-376426supporting
confidence: 78%
See 2 more Smart Citations
“…In addition, it was found that the distribution of the jagged structures for some reinforcements in the composites was different from that in the semisolid ingots prior to thixoforming, the jagged structures in the composites partially broke away from the core-shell structured particles and individually embedded in the matrix as shown by Figure 9, while they all compactly surrounded the core-shell particles similar to those shown by Figure 7. This implied that the bonding between the jagged structures and the shells was relatively weak, which was consistent to the result that there is always a gap between them and the gap is filled by Al matrix for the reinforcements in the semisolid ingots [14]. During thixoforming, the jagged structures peeled off from the inner core-shell structured particles and then moved away incorporating the liquid phase adjacent to them, resulting in the microstructure shown by Figure 9.…”
Section: Figures Of Metals-376426supporting
confidence: 78%
“…In appearance, the shell consisted of two layers, the inner light gray layer and the out gray layer. According to the EDS results, the composition of the inner white gray layers (points A in Figure 7) confirmed to that of τ1: 8-20 at.% Al, 50-62.6 at.% Si and 29.3 at.% Ti [14], while that of the out gray layers (points B) matched with the composition of (Al,Si) 3 Ti phase (the atomic ratio of (Al + Si)/Ti is about 3). The XRD results shown by Figure 8 also indicated that there were two phases of τ1 and (Al,Si) 3 Ti besides the phases of Al and Si in the matrix and the residual Ti phase.…”
Section: Figures Of Metals-376426mentioning
confidence: 53%
See 1 more Smart Citation
“…The authors combined the merits of PM and thixoforming and proposed a new technology named powder thixoforming for fabricating the Ti@Al 3 Ti p /Al matrix composite [ 12 ]. A green powder compact of Ti and Al powders is first obtained through blending and cold pressing of PM, and then is partially remelted to a semisolid state of the Al matrix alloy and thixoformed.…”
Section: Introductionmentioning
confidence: 99%
“…The authors investigated the microstructural evolutions of Ti-A356 and Ti-2024 compacts during partial remelting, and the effects of alloying elements such as Si, Cu, Zn, and Mg on the formation of the Ti@Al 3 Ti p [ 12 , 13 , 14 ]. The results indicated that Si element participated in the reaction between Ti powders and Al melt, and an ideal core-shell-structured Ti@(Al-Si-Ti) p with a thick and compact Al-Si-Ti compound shell was obtained in A356 alloys after being properly heated at semisolid temperatures.…”
Section: Introductionmentioning
confidence: 99%